An observer-based fixed-time position tracking strategy for DC torque motor systems. (August 2020) - Li, Guofei; Wu, Yunjie; Xu, Pengya
Highlights: In this paper, we present the fixed-time control method for position tracking of DC torque motor system. A novel fixed-time control strategy is proposed in this paper by employing two power state feedback parts to work separately with continuous transition, such property is effective in saving the control effort. A fixed-time extended state observer is designed to estimate the total disturbance in DC torque motor system. Abstract: The position tracking problem is investigated in this paper for DC torque motor system. A novel fixed-time control strategy is presented, the structure of which can be adjusted with continuous transition. A fixed-time extended state observer is designed to estimate the total disturbance. The proposed observer-based controller renders the position of DC torque motor track the desired signal in fixed time. Both disturbance observer and position tracking controller are fixed-time convergent. The bound of setting time can be determined regardless of initial states. Numerical simulation and experiment are carried out to validate the effectiveness of the proposed strategy.